External validation of the smartphone-based 6-minute walking test in patients with degenerative lumbar disorders undergoing epidural steroid injection - Ziga, Michal; Stienen, Martin N; Zeitlberger, Anna Maria; Voglis, Stefanos; Regli, Luca; Bozinov, Oliver; Maldaner, Nicolai (North American Spine Society journal, 2024)
BACKGROUND: The 6-minute walking test (6WT) has previously shown to be reliable and valid outcome measure in patients undergoing surgery for degenerative lumbar disorders (DLD). A role of 6WT in conservatively treated patients undergoing epidural steroid injection (ESI) remains unclear. METHODS: About 50 patients with DLD, scheduled for ESI were assessed by the smartphone-based 6WT and common paper-based patient-reported outcome measures (PROMs), including the Core Outcome Measures Index [COMI] back, Oswestry Disability Index (ODI) and Short Form Survey (SF-12). Pearson correlation coefficient (PCC) was used to define the relationship between 6WT and PROMs. Reliability of the 6WT was determined by intraclass correlation coefficient (ICC). Age- and sex-adjusted objective functional impairment (OFI) z-scores were calculated for each patient. RESULTS: A total of 50 patients (mean age 52 years, SD 13; 25% female), including 35 patients (70%) with lumbar disc herniation and 15 patients (30%) with lumbar spinal stenosis were included. The mean 6-minute walking distance (6WD) was 454.1 m (SD 89.1); the age- and sex-adjusted mean OFI z-score was -2.1 (SD 4.0). A total of 17 (34%) patients had mild, 8 (16%) moderate, and 4 (8%) severe OFI, while 21 (42%) had 6WT results within the normal population range (no OFI). The PCCs between the 6WD and VAS back pain were r=-0.30, ODI r=-0.43, COMI back r=-0.36, and PCS-12 r=0.51 (all p<.05). The ICC of the 6WT was β=0.92. CONCLUSIONS: This external validation in a patient cohort with DLD, which was managed conservatively, confirms the reliability and content validity of the 6WT with similar PCCs with PROMs compared to the original surgical cohort. The results confirm the 6WT as a valid and useful tool for assessing OFI in patients with DLD and a broad range of functional restrictions in an outpatient setting.